Factors affecting Malnutrition among Under Five Children in a Remote Community: A Case of Cabucgayan Municipality - De Paz, Pearl Irish Velicaria (Asian Journal of Multidisciplinary Studies, 2019)
Proper nutrition for children is every parent’s priority. In most continents, malnutrition comes in two guises such as under nutrition and over nutrition. In line with this, the researcher sought to identify the possible factors affecting malnutrition among the under-five children. The study was conducted in a remote community specifically in the Municipality of Cabucgayan, Biliran among the Top 3 barangays with the highest number of malnourished children. The data were gathered using the survey research design. Result shows that majority of the malnourished children were preschoolers, male children of Roman Catholic families, with 4-5 number of siblings, underweight and with family monthly income of 600Php-1000Php. Mostly usually ate rice, fish and junk foods except vegetables and the water used for drinking is untreated. Furthermore, the malnourished children had 8-12 number of hours of sleep per day, napped 3-4 hours a day and were not able to avail the scheduled immunizations and deworming. Moreover, environmental factors such as the source of drinking water is not safe and proper disposal of garbage is not observed by the households. The results of the study highlight the need to conduct information dissemination campaign on how to decrease the prevalence of malnutrition in remote communities.